1995
DOI: 10.1159/000262078
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Influence of Fluoride on the Equilibrating Calcium Phosphate Phase at a High Enamel/Acid Ratio

Abstract: Data obtained in a previous study suggested that brushite is the solubility-determining phase when enamel is first exposed to acid solution in a series of repeated equilibrations.Fluoride in solution might be expected to inhibit brushite formation, and experimental studies at low solid/solution ratio support this. We have now re-examined the effect at a very high ratio, in an attempt to mimic what happens in an enamel caries lesion. Powdered enamel was repeatedly exposed to HCl solution, 10-70 mmol/l, containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In such subsurface processes, the solid/solution ratio is very high and the question arises as to the relevance of the results of studies such as the present one. Although experiments at very high solid/solution ratios suggest persistent supersaturation with respect to hydroxyapatite, accompanied by brushite formation, even after repeated equilibration [13,41], non-equilibrium experiments suggest that dissolution of intact enamel, and also subsurface lesion formation, are controlled by a pK HA ≈ 58, close to that of hydroxyapatite [42][43][44][45][46][47][48]. This is probably because dissolution end-products are removed by diffusion instead of accumulating within the tissue, thus reducing the possibility that the interstitial fluid will become supersaturated.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In such subsurface processes, the solid/solution ratio is very high and the question arises as to the relevance of the results of studies such as the present one. Although experiments at very high solid/solution ratios suggest persistent supersaturation with respect to hydroxyapatite, accompanied by brushite formation, even after repeated equilibration [13,41], non-equilibrium experiments suggest that dissolution of intact enamel, and also subsurface lesion formation, are controlled by a pK HA ≈ 58, close to that of hydroxyapatite [42][43][44][45][46][47][48]. This is probably because dissolution end-products are removed by diffusion instead of accumulating within the tissue, thus reducing the possibility that the interstitial fluid will become supersaturated.…”
Section: Discussionmentioning
confidence: 93%
“…Analysis of solution data by chemical potential plots indicates that the solubility of enamel mineral and other biological apatites is often controlled by a phase with a lower Ca/P ratio than the apatite itself [11][12][13]. As a consequence, pI HA in a solution equilibrated with enamel tends to be pHdependent [12,14].…”
Section: Introductionmentioning
confidence: 99%
“…According to the above, three different methods of surface Fluorapatite was found to dissolve incongruently (nonstoistate analysis pointed to some changes that occurred on the chiometrically) (33, 38,[45][46][47][48], and the following sesurface of fluorapatite as a result of chemical interaction quence of ionic dissolution was established: fluorine, next with phosphoric acid. Briefly, the following changes took calcium, and afterward phosphate (67, 68).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in agreement with the statement of Weerheijm et al (1997) that fluoride may mask the spread of caries in enamel and dentin by encouraging remineralization only at the surface layer, thereby burying the underlying lesions. Many studies on remineralization in vitro also demonstrated that surface‐softened enamel remineralizes readily in the presence of fluoride in media, giving rise to the mineralized, less porous surface layer, whereas remineralization of subsurface demineralized lesions is becoming more difficult because of the restricted permeability of calcium and phosphate ions through the relatively mineralized surface layer (Pearce et al , 1995; Reynolds, 1997; Larsen and Richards, 2001). Thus innovation of technologies and measures for early diagnosis and management of the incipient caries lesions is still an urgent task to improve public health.…”
Section: Clinical Diagnosis and Histopathologic Validation Of Incipiementioning
confidence: 99%
“…The aim of adding calcium phosphate salts to toothpaste is also to achieve the calcium and phosphate enrichment for remineralization of early caries lesions. However, it was realized that, when the driving force for remineralization is too high, the resulting rapid precipitation on the surface may block the surface layer pores, thereby leaving the repair or consolidation of the body lesion incomplete (Pearce et al , 1995). In order to overcome this situation, the use of inhibitors for nucleation and crystal growth of calcium phosphates has been recommended, because stabilizing the supersaturated solution would help to generate high‐concentration gradients of calcium and phosphate ions and ion pairs into the subsurface lesion.…”
Section: Endogenous/exogenous Modulators Of Caries Lesion Formation Amentioning
confidence: 99%